2019
DOI: 10.3168/jds.2018-15680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Y-chromosome-linked TSPY, TSPY2, and PRAMEY genes in Taurus cattle, yaks, and interspecific hybrid bulls

Abstract: Domestic yaks (Bos grunniens) and domestic Taurus cattle (Bos taurus) are closely related. An interesting phenomenon in interspecific crossings is male sterility in the F 1 hybrid (yattle) and F 2 backcross, with no late meiotic cells or spermatids in the seminiferous tubules. The mammalian Y chromosome is crucial for spermatogenesis and male fertility. This study investigated the copy number variations and mRNA of Y-transitional region genes TSPY2 (testis specific protein, Y-linked 2 and testis-specific Y-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 43 publications
0
16
1
Order By: Relevance
“…Indeed, promoter and CGI hypermethylation associated with silencing PIWI/piRNA pathway genes PIWIL1, DDX4, PLD6, MAEL, FKBP6, RNF17, MOV10L1, TDRD1, TDRD5, and TDRD9 (Figure 2(c)), resulted in diminished production of pachytene piRNAs in yattle testes (Figures 3(d) and 4(e). This molecular connection with histologic observations of seminiferous tubules indicated that male infertility of yattle may be due to meiosis arrest at about the pachytene stage [7]. In contrast, PIWIL2, PIWIL4, EXD1, TDRD12 are involved in prepachytene piRNA production [65][66][67][68].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Indeed, promoter and CGI hypermethylation associated with silencing PIWI/piRNA pathway genes PIWIL1, DDX4, PLD6, MAEL, FKBP6, RNF17, MOV10L1, TDRD1, TDRD5, and TDRD9 (Figure 2(c)), resulted in diminished production of pachytene piRNAs in yattle testes (Figures 3(d) and 4(e). This molecular connection with histologic observations of seminiferous tubules indicated that male infertility of yattle may be due to meiosis arrest at about the pachytene stage [7]. In contrast, PIWIL2, PIWIL4, EXD1, TDRD12 are involved in prepachytene piRNA production [65][66][67][68].…”
Section: Discussionmentioning
confidence: 62%
“…F1 hybrid yattle and F2 backcross males are sterile while females are fertile. Seminiferous tubules of yattle contain few primary spermatocytes at the leptotene to pachytene stage and no spermatocytes beyond this stage [5][6][7]. Thus, the male infertility of yattle may be due to arrest of meiosis at about the pachytene stage [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSPY is expressed only in testicular tissue and may be involved in spermatogenesis. Previous studies demonstrated that TSPY1 has physiological functions in the proliferation and differentiation of spermatogonia during spermatogenesis [ 15 ]. Remarkably, TSPY1 is also involved in the initiation and development of many tumors by activating the PI3K/AKT and RAS signaling pathways by suppressing IGFBP3 expression [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The H3K9me1 and H3K9me2 histone demethylase JMJD1A is essential for spermatogenesis [21]. Previous studies have suggested that it is important to consider the epigenetic perspective when conducting research on cattle-yak spermatogenesis aiming to explore the mechanisms of cattle-yak sterility [5,22,23].…”
Section: Introductionmentioning
confidence: 99%